DARAH AMAN DAN PENDONOR DARAH SUKARELA (Safe Blood and Voluntary Non-Remunerated Blood Donors) - Teguh Triyono; Veronica Fridawati; Usi Sukorini; Budi Mulyono (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2014)
Safe blood was collected from safe, low risk donors with a related absence of infectious disease screening as well. WHO has statedthat to guarantee its safety, blood should only be collected from voluntary non-remunerated blood donors (VNBD) coming from a lowriskpopulation. The aim of this study was to know the blood donors’ profile in Fatmawati Hospital (FH), Jakarta and Dr. SardjitoHospital (SH), Yogyakarta by comparison The research was carried out by cross sectional study and data were obtained from the donor’sinformation records 2011-2013. The data were further descriptively analyzed and presented in tables and graphs. The Student’s t-testwas used to analyze the difference of percentage mean for VNBD per-month between two hospitals with p<0.05. Based on the blooddonor types, it was shown that most of the blood donors consisted of replacement persons. The mean of monthly VNBD percentage wassignificantly higher in FH than in SH. There was an increased VNBD percentage i.e. 32, 35, 54 (FH) and 12, 18, 22 (SH) respectively,within the year 2011, 2012 and 2013.